DPR Sebagai Pemediasi Antara CAONS, DTAR, Dan GCG Pada Harga Saham - Ainun Jariah (STIE Mandala Jember, 2021)
The company's performance projections are the focus of investors, especially investment decisions, funding decisions, and dividend policies, plus GCG which contribute to stock price volatility. The purpose of his research to detect the influence of CAONS, DTAR, and GCG individually and simultaneously on DPR and share prices, with DPR as a mediator. The number of samples 37 industry company registered on the BEI during 5 years since 2012. Analysis of data is path analysis and sobel tests for mediation variables. The research results explain that partially DTAR and GCG have a significant effect on DPR. but the share prices all three variables have no significant impact . Simultaneously CAONS, DTAR, and GCG have a significant impact on DPR and than no significant on share price. DPR has an effect and significant on share prices. Partially and simultaneously CAONS, DTAR, and GCG have no relationship to stock prices through DPR, and DPR is only able to mediate CAONS to stock prices. Keyword: CAONS, DTAR, GCG, DPR, and Stock Prices.